AAR450: Design I / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2018)
This course focuses on design fundamentals through the development of appropriate vocabulary, and interpretive and abstract thinking based upon visual perception, design elements, light, colour, form, space and order in design through several exercises in 2D and 3D compositions. Examples of built architectural works and other objects of art will be the point of reference.